Tales from Tennessee lawyers - Montell, William Lynwood, 1931- (University Press of Kentucky, 2005)
Lawyers have long been known as master storytellers, and those from Tennessee are certainly no exception. Veteran oral historian and folklorist William Lynwood Montell has collected tales from dozens of lawyers and judges from throughout the Volunteer State, ranging from stories of a custody battle over a family dog that garnered national media attention to the self-proclaimed "smartest man in Clay County." Recorded exactly as the lawyers tell them, these stories are sometimes funny, sometimes sad, sometimes raw and harrowing, but always remarkable. Far more than a collection of lawyer jokes.